2006
DOI: 10.1523/jneurosci.4430-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Potently Modulates Climbing Fiber→Purkinje Neuron Synapses: Role of Metabotropic Glutamate Receptors

Abstract: Consumption of alcoholic beverages produces alterations in motor coordination and equilibrium that are responsible for millions of accidental deaths. Studies indicate that ethanol produces these alterations by affecting the cerebellum, a brain region involved in the control of motor systems. Purkinje neurons of the cerebellar cortex have been shown to be particularly important targets of ethanol. However, its mechanism of action at these neurons is poorly understood. We hypothesized that ethanol could modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 63 publications
3
54
1
1
Order By: Relevance
“…However, results from studies from our laboratory show that, in acute slices, synaptic NMDA currents from deep-layer PFC neurons are reliably inhibited by moderate (44 mM) concentrations of ethanol whereas those generated by AMPA or GABA A receptors are mostly unaffected (our unpublished observations). These findings are generally consistent with other studies showing that ethanol has little effect on most AMPA-mediated EPSCs (Lovinger et al, 1989;Weiner et al, 1999) (but see Mameli et al, 2005;Carta et al, 2006) and has variable effects on GABA-mediated currents (for review, see Weiner and Valenzuela, 2006). Importantly, NMDA-dependent response processes are consistently reported to be inhibited by ethanol including those from hippocampus (Lovinger et al, 1990), posterior cingulate (Li et al, 2002), nucleus accumbens (Nie et al, 1994), and amygdala (Roberto et al, 2004).…”
Section: Ethanol Modulation Of Pfc Persistent Activitysupporting
confidence: 88%
“…However, results from studies from our laboratory show that, in acute slices, synaptic NMDA currents from deep-layer PFC neurons are reliably inhibited by moderate (44 mM) concentrations of ethanol whereas those generated by AMPA or GABA A receptors are mostly unaffected (our unpublished observations). These findings are generally consistent with other studies showing that ethanol has little effect on most AMPA-mediated EPSCs (Lovinger et al, 1989;Weiner et al, 1999) (but see Mameli et al, 2005;Carta et al, 2006) and has variable effects on GABA-mediated currents (for review, see Weiner and Valenzuela, 2006). Importantly, NMDA-dependent response processes are consistently reported to be inhibited by ethanol including those from hippocampus (Lovinger et al, 1990), posterior cingulate (Li et al, 2002), nucleus accumbens (Nie et al, 1994), and amygdala (Roberto et al, 2004).…”
Section: Ethanol Modulation Of Pfc Persistent Activitysupporting
confidence: 88%
“…Many biological phenomena contribute to ethanolinduced responses. These include the involvement of neuropeptide-Y related pathways, [1][2][3][4] glutamate receptors, 5,6 GABA receptors, 7,8 the cAMP signalling pathway, 9,10 the BK potassium channel, SLO-1 [11][12][13] , and membrane perturbation. 14 Many genes and proteins are conserved between Caenorhabditis elegans and humans, including many of those that have been identified as playing a possible role in the effects of ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous research has shown that ethanol can directly affect various aspects of brain development in the fetus. [2][3][4] Similarities in development between humans and mice have led to wide usage of fetal mice as models for human developmental diseases. Alcohol-exposed pregnant mice have previously been used to study the emergence of FASD during fetal development.…”
mentioning
confidence: 99%